Study of in vitro regeneration protocol of gerbera (Gerbera jamesonii Bolus) grown in Bangladesh - Hossain, Syed Akib (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.